ROLE OF CARDIAC MAGNETIC RESONANCE IN DIAGNOSIS AND TREATMENT OF BALL THROMBUS IN LEFT ATRIUM – TRUST BUT VERIFY! – CASE REPORT - Ted Trajcheski; Lulzim Brovina; Biljana Zafirova; Saso Josimovski (Macedonian Academy of Sciences and Arts, 2023)
Male patient with left atrial cardiac mass was in need of a quick diagnosis for individualized and effective treatment. Transthoracic echocardiography showed presence of а giant left atrial cardiac mass with atypi cal location for thrombus. Cardiac Magnetic Resonance (CMR) Imaging was performed for histological discrimination, and showed a large cardiac mass wall attached in the left atrium, homogeneous, with diameter of 3.4cm x 3.2cm. Late Gadolinium Enhancement sequences revealed black avascular tissue without signal, confirming the characterization of a thrombus. The patient refused hospital initiation of low molecular weight heparin treatment and started treatment with Rivaroxaban. Six weeks later he presented with NYHA class II, almost complete dissolving of the throm bus on CMR scan. Seven months from the initial CMR scan, echocardiography screen was done showing complete absence of the left atrial mass. With this case report we have demonstrated the significance of the CMR as one step further in the precise diagnostics of cardiac masses, solving critical clinical dilemma.
Keywords: left atrial cardiac mass; ball thrombus; CMR; Echocardiography